Exercise‐induced dynamic mitral regurgitation is associated with outcomes in patients with ischaemic cardiomyopathy - Maximilian Spieker; Jonas Sidabras; Hannah Lagarden; Lucas Christian; Niklas Günther; Stephan Angendohr; Alexandru Bejinariu; P. Christian Schulze; Roman Pfister; Can Öztürk; Ralf Westenfeld; Patrick Horn; et al. (ESC Heart Failure)
Abstract Aims Ischaemic mitral regurgitation (MR) is a dynamic condition influenced by global and regional left ventricular remodelling as well as mitral valvular deformation. Exercise testing plays a substantial role in assessing the haemodynamic relevance of MR and is recommended by current guidelines. We aimed to assess the prevalence, haemodynamic consequences, and prognostic impact of dynamic MR using isometric handgrip exercise. Methods and results Heart failure patients with ischaemic cardiomyopathy and at least mild MR who underwent handgrip echocardiography at the University Hospital Duesseldorf between January 2018 and September 2021 were enrolled. Patients were followed‐up for 1 year to assess a combined endpoint including all‐cause mortality, heart failure hospitalization, mitral valve surgery/interventions, ventricular assist device implantation and heart transplantation. One hundred thirty‐three patients with ischaemic cardiomyopathy were included (age 75 ± 10 years; 21% female; LVEF 35 ± 9%). At rest, 70 patients (53%) presented with mild MR, 54 patients had moderate MR (41%), and 9 patients (7%) showed severe MR. Twenty‐five patients (20%) with non‐severe MR at rest, developed severe MR during handgrip exercise. Patients with dynamic MR had larger left atrial dimensions, increased wall motion score index and larger tenting area at rest. Multivariate analysis identified MR severity during exercise [HR 1.998 (1.367–2.938)] and exercise TAPSE [HR 0.913 (0.853–0.973)] as predictors of the combined endpoint. Conclusions The haemodynamic changes provoked by isometric exercise unmasked dynamic severe MR in a significant number of patients with non‐severe MR at rest. These data may have implications for therapeutic decision‐making in symptomatic patients with non‐severe MR at rest.